Enhancing Blowfish file encryption algorithm through parallel computing on GPU - Mahajan, Tejal; Masih, Shraddha (2015 International Conference on Computer, Communication and Control (IC4), 2015)
Parallel computing can provide fast execution of the program as compared to sequential computing. Graphical Processing Unit can be used for parallel computing as it gives the advantage of multiple cores. Purpose of parallel implementation of Blowfish cryptography algorithm is to improve the speed up of encryption and decryption so that large files also can be communicated on the network in secure and efficient way. This paper demonstrates the way of implementing Blowfish cryptography algorithm on GPU for improving performance. This implementation uses GPGPU and CUDA. CUDA is used as a programming model for implementing on the GPU. The experiment shows multifold difference in performance of CPU and GPU in encryption-decryption of large files.